Benjamín Marticorena Castillo: Public policies on science and technology in Peru: Challenges, lessons learned, and paths for a new generation - Vásquez Rodríguez, Rafael (2025)
Dr. Benjamín Marticorena Castillo holds a PhD in Physics from the University of Grenoble, France, which awarded him the distinction of “Knight of the Legion of Honor.” He was President of Concytec between 2001 and 2006, during which time the Framework Law for the National System of Science, Technology, and Innovation (Sinacyt) was approved in 2004 and the Concytec Law (2005). He has taught at several universities in Peru and abroad. He is the author of several books, his most recent publication being “Navegación Incesante” (Ceaseless Navigation), a collection of essays that remain strikingly relevant despite the years that have passed since they were written. He is also the author of scientific articles in the fields of energy, science, technology, and STI public policy. He is an international consultant and member of various scientific organizations. In 2020, he was reappointed as President of Concytec, where he promoted the approval and implementation of the SINACTI Law. He has held institutional positions at IPEN, the Bartolomé de las Casas Center in Cusco, SEPIA, ANCYT, among many other entities. His extensive career in support of science, technology, and innovation includes the implementation of the SciELO Peru electronic library and countless contributions from the perspective of national development and ethics in public and private service.